Penerapan Teknologi Augmented Reality Sebagai Media Pembelajaran Ilmu Tajwid Berbasis Android - Alip Adhani; Muhamad Azrino Gustalika; Iqsyahiro Kresna A (JURIKOM (Jurnal Riset Komputer), 2022)
Mutiara Islam Integrated Islamic Elementary School is a superior school for students of Islamic religious education. At this school, it is related to Islamic religious education, one of which is the basics of tajwid. The science of recitation is very important in reading the Qur'an, because one of the things that needs to be done is to apply it when reading the Qur'an to understand the science of recitation. Different levels of students' understanding of the applied learning process methods. Building interactive learning media in which there is an attractive visualization further increases students' enthusiasm for learning and increases students' understanding of the material being taught. This research builds interactive learning media of recitation based on augmented reality with software application development adopting the Android Mobile Multimedia Development Life Cycle (MDLC) method in the form of a computer application. The tracking method of augmented reality (AR) technology that can be used in this research is marker-based tracking. Based on the results of functional testing shows that the application is functioning properly. In the test results, the angle shows a tilt angle of 20 degrees with a high pass rate and a maximum angle limit of 80 - 90 degrees using smartphones with different specifications. The results of the analysis of user satisfaction, good test results were carried out through a questionnaire with a total of 30 respondents giving an average SUS score of 86.8, which leads to the conclusion that the application can be accepted by users with a Excellent adjective rating category